Lower NPAS3 expression during the later stages of abnormal lung development in rat congenital diaphragmatic hernia - Terra, Patrícia Daniela Pereira (2015)
Purpose Congenital diaphragmatic hernia (CDH) is characterized by a developmental defect in the diaphragm, pulmonary hypoplasia and pulmonary hypertension. NPAS3 is a PAS domain transcription factor regulating Drosophila tracheogenesis. NPAS3 null mice develop pulmonary hypoplasia in utero and die after birth due to respiratory failure. We aimed to evaluate NPAS3 expres- sion during normal and abnormal lung development due to CDH. Methods CDH was induced by administering 100 mg/ml nitrofen to time-pregnant dams on embryonic day (E) 9 of gestation. Lungs were isolated on E15, E18 and E21 and NPAS3 localization was determined by immunohisto- chemistry and quantified using Western blotting. Results We found that only E21 hypoplastic CDH lungs have reduced expression of NPAS3 in the terminal sac- cules. Western blotting confirmed the down-regulation of NPAS3 protein in the nitrofen-induced hypoplastic lungs. Conclusions We demonstrate for the first time that ni- trofen-induced hypoplastic CDH lungs have reduced NPAS3 expression in the terminal saccules during the later stages of abnormal lung development. Our findings suggest that NPAS3 is associated with pulmonary hypoplasia in CDH.